A tool for the analysis of the efficiency of a parallel LU factorization algorithm - Raimondas Čiegis; Vadimas Starikovičius (Lietuvos Matematikos Rinkinys)
This paper considers issues on the design of a tool for the analysis of a parallel LU factorization algorithm. The costs of data communication are included into the theoretical model. Problems of defining the optimal number of processors and efficient data distributions among processors are investigated. Results of computational experiments are given.